Nipple Dermatitis as a Localized Manifestation of Atopic Dermatitis: A Case Report - Ifen Ayu Malinda; Kristo Alberto Nababan (Indonesian Journal of Global Health Research, 2025)
Nipple dermatitis is an inflammatory skin condition affecting the areolar and nipple region, most commonly associated with atopic dermatitis (AD). It presents significant diagnostic challenges due to its overlapping features with other conditions such as irritant contact dermatitis, allergic contact dermatitis, Paget’s disease, and cutaneous . This case report aims to present the diagnostic approach and management of nipple dermatitis in an adolescent patient, highlighting its clinical relevance and differential diagnosis.This case report discusses a 16-year-old female presenting with bilateral nipple dermatitis, initially suspected to have malignancy. Comprehensive evaluation including cytology, ultrasonography, and KOH examination ruled out malignancy and fungal infection. A working diagnosis of nipple dermatitis secondary to atopic dermatitis was established. The patient responded well to topical corticosteroids, emollients, antihistamines, and supportive care. This case highlights the importance of accurate clinical assessment and individualized treatment in managing nipple dermatitis, particularly in adolescents. Early identification and appropriate intervention can prevent chronicity and improve patient quality of life.